Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Motivasi Kerja, dan Komunikasi Organisasi Terhadap Kinerja Karyawan - Resa Mustika; Andri Kusmayadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Employee performance is a key factor in organizational success, influenced by various aspects such as leadership style, work environment, motivation, and organizational communication. This study aims to analyze the effect of these four variables on employee performance at PT. Multi Artha Abadi. A quantitative research method was applied using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with SmartPLS software. The respondents consisted of 120 employees selected through purposive sampling. The analysis results show that all independent variables have a positive and significant effect on employee performance. Motivation is identified as the most dominant factor, followed by organizational communication, leadership style, and work environment. The R-square value of 0.939 indicates that 93.9% of the variation in employee performance can be explained by these four variables. These findings emphasize the importance of an integrated strategy that includes strengthening leadership, creating a conducive work environment, enhancing motivation, and improving organizational communication. The study concludes that well-planned human resource management can significantly improve performance. The practical implication is that companies need to design HR policies that prioritize leadership development, employee well-being, achievement motivation, and effective communication systems.